The unique and valuable soft tissue free flap in head and neck reconstruction: Lateral arm. (July 2018) - Kang, Stephen Y.; Eskander, Antoine; Patel, Krupal; Teknos, Theodoros N.; Old, Matthew O.
Highlights: The lateral arm free flap is a versatile soft tissue flap for head and neck reconstruction. The lateral arm provides excellent color match and contour for many defects of the head and neck. The anatomy, surgical technique, indications, and advantages of the lateral arm flap are reviewed. Abstract: While the lateral arm free flap has been well described, there is a relative paucity in its use compared to other free flaps and regional flaps. The lateral arm free flap is a unique soft tissue free flap that provides several reconstructive advantages in head and neck reconstruction: excellent contour and color match to facial skin, well compartmentalized fat, donor nerves for nerve grafting, and the ability to two-team harvest and close the donor site without a skin graft. A detailed anatomic and harvest technique is described, along with indications and advantages of using lateral free flap for head and neck reconstruction. A scoping literature review was also conducted to tabulate indications, overall success and complications of the flap. The lateral arm flap is a primary option for defects requiring soft tissue reconstruction in the head and neck.